Tagger: Practical PFC Deadlock Prevention in Data Center Networks - Hu, Shuihai; Zhu, Yibo; Cheng, Peng; Guo, Chuanxiong; Tan, Kun; Padhye, Jitu, Kai Chen (CoNEXT, 2017)
Remote Direct Memory Access over Converged Ethernet (RoCE) deployments are vulnerable to deadlocks induced by Priority Flow Control (PFC). Prior solutions for deadlock prevention either require significant changes to routing protocols, or require excessive buffers in the switches. In this paper, we propose Tagger, a scheme for deadlock prevention. It does not require any changes to the routing protocol, and needs only modest buffers. Tagger is based on the insight that given a set of expected lossless routes, a simple tagging scheme can be developed to ensure that no deadlock will occur under any failure conditions. Packets that do not travel on these lossless routes may be dropped under extreme conditions. We design such a scheme, prove that it prevents deadlock and implement it efficiently on commodity hardware.